Strategi Penetapan Harga Sewa Gedung Guna Meningkatkan Omzet Sewa Gedung - Fauzi, Muhammad; Sri Astutik, Wahyuni; Ari Sumaryati, Sri (JUMBA (Jurnal Manajemen, Bisnis, dan Akuntansi), 2023)
The purpose of this research is to describe the pricing method used by the Kediri Regency Convention Hall Building. This type of research uses qualitative research because the data analysis is in the form of interviews and direct observation for information from sources. The result of the research is the setting of rental prices that are too high because of the inaccurate classification of costs according to the main functions of the company's activities.